2012
DOI: 10.1007/s10571-011-9793-z
|View full text |Cite
|
Sign up to set email alerts
|

NPY and Stress 30 Years Later: The Peripheral View

Abstract: Almost 30 years ago, neuropeptide Y (NPY) was discovered as a sympathetic co-transmitter and one of the most evolutionarily conserved peptides abundantly present all over the body. Soon afterward, NPY’s multiple receptors were characterized and cloned, and the peptide’s role in stress was first documented. NPY has proven to be pivotal for maintaining many stress responses. Most notably, NPY is known for activating long-lasting vasoconstriction in many vascular beds, including coronary arteries. More recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 113 publications
2
108
0
4
Order By: Relevance
“…Neuropeptide Y (NPY) is a 36 amino acid peptide which belongs to the pancreatic polypeptide (PPY) family and exhibits 70 % amino acid sequence homology with peptide YY (PYY) and 50 % to PPY [11]. It is the most abundant neuropeptide in the mammalian brain and plays an important role in the feeding behavior, depression and stress, and the release of hypothalamic and pituitary hormones [12]. NPY is costored and co-released with norepinephrine in the sympathetic nerve endings.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptide Y (NPY) is a 36 amino acid peptide which belongs to the pancreatic polypeptide (PPY) family and exhibits 70 % amino acid sequence homology with peptide YY (PYY) and 50 % to PPY [11]. It is the most abundant neuropeptide in the mammalian brain and plays an important role in the feeding behavior, depression and stress, and the release of hypothalamic and pituitary hormones [12]. NPY is costored and co-released with norepinephrine in the sympathetic nerve endings.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptide Y is thought to be pivotal in the stress response, with functions that include increasing food intake and fat storage, reducing anxiety, stress, and the perception of pain, and affecting circadian rhythms. 35 One immunohistochemical study demonstrated an increase in neuropeptide Y immunoreactive cells in the hippocampus, associated with increase in locomotion and weight as compared with control in maternally separated rats treated with a single acupuncture point. 36 Additional potential mechanisms of action stem from evidence that acupuncture can increase adrenocorticotropic hormone, a substance integral to the stress response, β-endorphins-the neurotransmitters associated with pain relief and a sense of well-being-as well as the neurotransmitters serotonin, dopamine and norepinephrine, all important targets in the psychiatric treatment of depression and anxiety.…”
Section: Possible Biologic Mechanisms For Acupuncture Effectsmentioning
confidence: 99%
“…CRF is a neuropeptide and gut hormone that is intimately related to stress, and there is considerable evidence that activation of peripheral CRF receptors contributes to stress-related alterations of gut physiology [126]. NPY may likewise be involved because it appears to mediate the effects of stress on many physiological systems including the gastrointestinal and immune systems [128,129]. For instance, deletion of NPY alters gastrointestinal, feeding and corticosterone responses to restraint stress, exaggerates stressinduced defaecation and reduces food intake [128].…”
Section: Effect Of Npy To Protect From the Impact Of Stress On The Gumentioning
confidence: 99%